2021
DOI: 10.1021/acsanm.1c02754
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenated Silicon Nanoclusters with a Permanent Electric Dipole Moment for the Controlled Assembly of Silicon-Based Nanostructures

Abstract: While silicon nanoclusters have extensively been used for their outstanding properties for many decades, never before their dipole moment has been exploited for any application. Here, we have succeeded in producing hydrogenated silicon nanoclusters with a strong permanent electric dipole moment. This dipole moment allows us to use electric fields in order to orient and guide individual clusters. As a first example, we 1 demonstrate the catalyst-free one-by-one self-assembly of one of the thinnest silicon nanow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 58 publications
(113 reference statements)
3
13
0
Order By: Relevance
“…31,32 Interestingly, hydrogenated Si-NCs also show dipole moments, which are important for the controlled assembly of silicon-based nanostructures. 37 With the work presented here, it is now additionally shown that isolated Si N nanoclusters in the gas phase are also polar despite their compact, near-spherical shape.…”
Section: Discussionsupporting
confidence: 52%
“…31,32 Interestingly, hydrogenated Si-NCs also show dipole moments, which are important for the controlled assembly of silicon-based nanostructures. 37 With the work presented here, it is now additionally shown that isolated Si N nanoclusters in the gas phase are also polar despite their compact, near-spherical shape.…”
Section: Discussionsupporting
confidence: 52%
“…This means that all SiNCs considered here are neutral in the afterglow. We underline that we have already given experimental proof for this conclusion regarding our specific nanoclusters [8]: After their creation, our SiNCs had to travel a certain distance before laser detection. Even if they had been charged with only one single elementary charge, they should have traveled this distance within 9 µs because of the applied electric DC field.…”
Section: Cluster Preparationmentioning
confidence: 62%
“…Since the experimental details have been published elsewhere [8], we will only concentrate on some major features here. Inside a 0.02 m 3 vacuum chamber, an RF (13.56 MHz) CCP discharge was generated (Cesar 133 RF power supply) at low pressure (10 to 15 Pascals) between a grounded and a powered electrode.…”
Section: Cluster Preparationmentioning
confidence: 99%
See 2 more Smart Citations